South Africa’s Involvement in Zimbabwe’s Suspension from the Commonwealth of Nations (Tema Central) - Petrica, Dan (2021)
This article delves upon Zimbabwe’s 2002 suspension from the Commonwealth of Nations and the relentless efforts of South Africa and other peers to get that suspension lifted, in the context of continuous rebuttals from states such as the UK and Australia. The research piece touches primarily upon the underlying motives for the said suspension, as well as the reasoning behind the bandwagoning of nations on the ongoing issues plaguing Zimbabwe in the early 2000s. Furthermore, it tangentially covers themes such as: the balance within the Commonwealth, global North versus South interpretations of democracy – and the realities they produce, and the rationale of two-sided post-colonial narratives. In our endeavour we have used a series of primary and secondary literary sources. Our conclusion is that South Africa gave primacy to its own foreign policy objectives, and thereby, allowed democracy to continue to disintegrate in Zimbabwe. Our research piece purposefully lacks the classical structure one might expect, for we consider that the chosen style of organizing information best befits the general public and specialized reads alike.